Aplikasi Traffic Monitoring Server Menggunakan SMS - Ilona, Clarissa (Bina Nusantara University, 2010)
This study aims to build traffic monitoring application that can help network administrator to monitor server anytime and anywhere, by using SMS. Things to be monitored are data traffic and server network connection. Literature study, and field study were done before designing the application.The result is application that can send and receive SMS to / from network administrator, check the connection to the server, and respond to network administrator in a relatively fast time when the connection to the server having problem.In addition, the application can monitor the details of data packets at the server and displays the bandwidth based on protocol. The details of data packets can also be sent via SMS. The conclusion is that traffic monitoring application is very useful because it can help network administrator to monitor servers anytime and anywhere. It is suggested to add a remote feature in this application.